The Role of Electronic Medical Records as Evidence in Medical Disputes in Hospitals - Devina Anggraeni; Muhammad Ikhsan (SOEPRA, 2019)
Medical Record is a file that contains records and other documents such as patient identification, examination, the treatment that has been given to the patient. Based on the Minister of Health No. 269/MENKES/PER /III / 2008 concerning the medical record that there are two types of medical records that conventional medical records and electronic medical records. With the absence of a strong legal basis related to the setting of electronic medical records, but in reality, many hospitals are using electronic medical records which raised the question, how the role of electronic medical records as evidence in the medical dispute that occurred in the hospital ?. This study uses Descriptio with the normative juridical approach. The data used is qualitative. This is done to get an overview of the roles of electronic medical records as evidence in the medical dispute in the hospital. Electronic medical records in the case of medical dispute resolution in the hospital can not be made as evidence in the medical case settlement, because the regulations related to the use of electronic medical records alone do not yet have a clear legal basis.